(Almost) all evidence is higher-order evidence. (8th May 2022) - Hedden, Brian; Dorst, Kevin
Abstract: Higher-order evidence is evidence about what is rational to think in light of your evidence. Many have argued that it is special – falling into its own evidential category, or leading to deviations from standard rational norms. But it is not. Given standard assumptions, almost all evidence is (in part) higher-order evidence.